'We're keeping on top of the students': making sense of test data with more informal data in a grade-level instructional team. Issue 1 (1st January 2018) - Wardrip, Peter S.; Herman, Phillip
Abstract: Internationally, there has been a policy push for using student data for instruction. Yet, research has noted few examples of actually understanding how this data-use practice takes place. This study presents a case of an instructional data team making sense of student data. The study shares data to show how teachers' process for using data to inform their instructional choices is an interpretive one. The study also highlights the fact that, to make sense of test data that are often incapable of capturing backstories of students' work in school, teachers draw upon informal data that they glean from their observations of and interactions with students. The collective data in the heads of teachers emerge through data team discussions. We conclude with implications for policy, professional learning, and teacher development.